Lean UX: Applied PSSUQ to Evaluate Less-ON UI/UX Analysis and Design - Rio Andika Malik; Marta Riri Frimadani (International Journal of Advances in Data and Information Systems, 2023)
Indonesian start-up growth continues to show upward growth. Behind the upward movement of change are success statistics that develop contradictions. According to start-up statistics, about 90% of start-ups fail. Up to 75% of unicorn start-ups believe his excellent UI/UX design can boost start-up valuations and additional investment capital. Less-On is a tutoring provider that acts as an intermediary between teachers and students. This research is done by integrating the process of Lean UX methodology into each process present in each phase of software development. The results obtained from this research are final prototypes that have been validated in terms of criticism and suggestions through questionnaires in the form of lessons on start-up branding. The positive user experience and excellent usability will help further the development of the tutor booking application prototype. This plays an important role in the acceptance, satisfaction and efficiency of using this Less-ON application. The user interface has excellent usability for users tested using the PSSUQ, with an overall average score of 2.136, indicating system usability, information quality, interface quality, and overall Satisfaction-based demonstrates that the system is highly acceptable.